Water-sediment partitioning of flumequine and florfenicol, two antibiotics used in salmon aquaculture in Chile - Jara Vergara, Bibiana Andrea; Srain, Benjamin M.; Aranda, Mario; Fernandez, Camila; Pantoja-Gutierrez, Silvio; Mejanelle, Laurence (My University, 2022)
The water-sediment partitioning of flumequine and florfenicol, two antibiotics used in salmon aquaculture is a critical driver of their fate and environmental impact. Batch experiments, were carried out using pure water or seawater, with or without sediment, and at summer and winter temperatures of Chilean fjords. Log K-d (partition between water and sediment) of florfenicol in seawater varied from 0.62 +/- 0.69 to 0.67 +/- 0.13, and Log K-OC (partition between water and organic fraction of sediment) from 2.15 +/- 0.29 to 2.19 +/- 0.13. Difference between K-OC and the octanol-water partition constant (KOW) showed that for florfenicol, adsorption onto the surface of particles was more significant than the absorption driven by hydrophobicity whilst hydrophobic absorption was a major driver of flumequine sorption. Flumequine Log K-d (0.92 +/- 0.25 to 1.36 +/- 0.10) and Log K-OC (from 2.44 +/- 0.25 to 2.89 +/- 0.10) demonstrated its greater affinity than florfenicol to particles and potential accumulation into marine sediments.
Keywords: emerging pollutant; sorption; florfenicol; flumequine; k-d and k-oc